DEVELOPMENT OF WEB-BASED INTERACTIVE LEARNING MEDIA ON THE TOPIC OF LIVING ORGANISM ADAPTATION USING THE TUTORIAL METHOD - R Ati Sukmawati; Khairunnisa Khairunnisa; Ratna Yulinda; Muhammad Hifdzi Adini; Harja Santana Purba; Nur Syifa Ningrum (Universitas Lambung Mangkurat, 2024)
Web-based interactive learning media is a computer-based learning media, which was developed to provide feedback on user activities. The aim of this research is to develop appropriate web-based interactive learning media, on material on the adaptation of living things, using the tutorial method. The type of research used is Research and Development with the ADDIE development model, which has stages of analysis, design, development, implementation and evaluation. The test subjects were sixth grade students at SDN Sungai Miai 11 Banjarmasin. Data collection techniques were carried out using questionnaire techniques and test techniques. The data analysis techniques used are descriptive statistics and n-gain. The result of this research is web-based interactive learning media on the adaptation of living things using the tutorial method, which was developed using HTML, CSS, Bootstrap, Javascript, JSON, Firebase, Canva and Netlify technology. The results of the analysis show that the learning media material content is valid, in the very high category, while the media validity value is in the high category. The results of the practicality test show that the media is declared practical, with student responses on average agreeing. The media is also declared effective, with an n-gain value for medium qualifications and average student learning outcomes above the KKM. Therefore, web-based interactive learning media, on the adaptation of living things, using the tutorial method is declared suitable for use as supporting media in science learning in sixth grade.